The Efforts to Improve Teachers' Teaching Skills in Implementing Cooperative Learning Through Classroom Supervision: Upaya Meningkatkan Keterampilan Mengajar Guru Dalam Menerapkan Cooperative learning Melalui Supervisi Kelas - Syam Sahri (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2021)
The background of this research is the lack of a class teacher teaching skills improvement program. Therefore, it is necessary to improve teacher teaching skills through classroom supervision at UPT SDN 20 Sitiung, Dharmasraya, West Sumatra Province in the 2020/2021 school year. The purpose of this study was to improve classroom teacher skills through cooperative learning. The method used is